Risk of second brain tumour after conservative surgery and radiotherapy for pituitary adenoma. Issue 6838 (23rd May 1992) - Brada, M.; Ford, D.; Ashley, S.; Bliss, J. M.; Crowley, S.; Mason, M.; Rajan, B.; Traish, D.
Abstract : OBJECTIVE--To assess the risk of second brain tumour in patients with pituitary adenoma treated with conservative surgery and external beam radiotherapy. DESIGN--Long term follow up of a cohort of patients with pituitary adenoma and comparison of tumour occurrence with population incidence rates. SETTING--The Royal Marsden Hospital. SUBJECTS--334 patients with pituitary adenoma treated with conservative surgery and radiotherapy (median dose 45 Gy) and followed up for 3760 person years. MAIN OUTCOME MEASURES--Second intracranial tumour and systemic malignancy. RESULTS--Five patients developed a second brain tumour: two had astrocytoma, two meningioma, and one meningeal sarcoma. The cumulative risk of developing a second brain tumour over the first 10 years after treatment was 1.3% (95% confidence interval 0.4% to 3.9%) and over 20 years 1.9% (0.7% to 5.0%). The relative risk of a second brain tumour compared with the incidence in the normal population was 9.38 (3.05 to 21.89). There was no excess risk of any other type of second primary malignancy. CONCLUSIONS--There is an increased risk of second intracranial tumour in patients with pituitary adenoma treated with surgery and radiotherapy. Although radiation is likely to be the most important factor contributing to the excess risk, further study is required in a cohort of similar patients not receiving radiation.